Proposal of a nonlinear piezoelectric coupling term to energy harvesting interactions - Tusset, Ângelo Marcelo; Iliuk, Itamar; Rocha, Rodrigo Tumolin [UNESP]; Piccirillo, Vinícius; Balthazar, José Manoel [UNESP]; Felix, Jorge Luiz Palacios; Brasil, Reyolando Manoel Lopes da Fonseca Rebello (Springer Nature, 2015)
Nowadays, new technologies have triggered the needs of new energy sources, smaller and more efficient, so the research about energy harvesting has increased substantially. Several researchers have developed the conversion of wasted mechanical energy to electrical energy using piezoelectric materials as a transducer. This chapter proposes a mathematical model for the constitutive equation of a piezoelectric transducer. Experimental results involving piezoelectric elements were considered. The proposed mathematical model allows a considerably better description. The results are closer to those obtained in a real system, reducing inaccuracy of predictive behaviour of the piezoelectric energy harvesting system. In this work, the numerical simulations show a significant difference between results obtained with the proposed model and other models available in literature.